Anatomía foliar de tres especies de Bromeliaceae como componentes de la dieta del oso andino (Tremarctos ornatus) en el Parque Nacional Podocarpus. - Vallejo Ochoa, Natalia Salomé (2014)
The Andean bear Tremarctos ornatus, is a key species for conservation of paramos and andean forests ecosystem. Therefore, we studied the anatomic structure of the Puya eryngioides, Puya maculata and Puya nitida, which constitute the main diet of the Andean bear in the Podocarpus National Park (PNP). Ten leaves of each species of paramos of PNP were collected and after in the laboratory each leaf was divided into middle and basal part; and were fixed in FAA (formaldehyde 5ml, 5ml acetic acid and ethyl alcohol 70% 90ml), and cutting, assembly and analysis was done; the technique used was cut freehand, marinated and hand scraping the epidermis. The leaf epidermis of the three species are composed of rectangular cells, nearly straight anticlinal walls sinuous, thickened. The scales (trichomes) in the three species is distributed in longitudinal rows and consist of shields and wings in P. eryngiodes and P. nitida; its presence is related to the absorption of water and nutrients, and reducing perspiration normal basic qualities of the vegetable species develops.